Understanding Relations Among Drinking and Hookup Motives, Consequences, and Depressive Symptoms in College Students. (June 2020) - Winkeljohn Black, Stephanie; Owen, Jesse; Soler, Nehemiah; Fincham, Frank
In this longitudinal study ( N  =   98), we examined whether drinking for suppression reasons moderated the relation between depressive symptoms and hooking up for self-affirmation reasons and negative hookup consequences. No moderation was found for hooking up for self-affirmation reasons, but the effect for negative hookup consequences approached significance. When drinking for suppression reasons is low, participants with fewer depressive symptoms reported more negative consequences, and participants with more depressive symptoms reported fewer negative consequences 2 months later. Results are discussed within the context of sex education and mental health programming for young adults.